The Effectiveness of a Health Literacy Development Program in Coronavirus 2019 Prevention for Older Adults with Diabetes Mellitus in Phra Nakhon Si Ayutthaya Province - Werunat, Monsicha; Moolsart, Sutteeporn; Tipkanjanaraykha, Kitsanaporn (Journal of The Royal Thai Army Nurses, 2023)
The quasi-experimental research was a two-group pretest-posttest design. The purposes of the research were to study the effects of a health literacy development program in Coronavirus 2019 prevention for older adults with diabetes mellitus on health literacy and Coronavirus 2019 preventive behavior. The samples were older adults with uncontrolled type 2 diabetes patients. They all were living in Phra Nakhon Si Ayutthaya Province.The sample was selected by systematic random sampling and put into an experimental and a comparative groups with 35 people each. Research instruments were 1) a health literacy development program in Coronavirus 2019 prevention for older adults with diabetes that was based on the concept of health literacy development for older adults by Manafo and Wong. The 6-week activities were workshops and knowledge reviewing by LINE application. 2) A handbook of health literacy in Coronavirus 2019 prevention; and 3) questionnaires on health literacy and Coronavirus 2019 preventive behavior. The tools were validated by 5 experts and the content validity indexes were .95 and 1.00, respectively. Kuder-Richardson-20 of the health literacy questionnaire was .85. Cronbach’s alpha coefficient of the Coronavirus 2019 preventive behavior was .79. Data were analyzed by descriptive statistics and a t-test. The result revealed as follows: after enrolling in the program, the health literacy and preventive behavior in Coronavirus 2019 prevention of the experimental group was better than before enrolling in the program, and the comparative group at p-value < .01